2020
DOI: 10.1093/jnci/djaa046
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Before, During, and After Chemotherapy for High-Risk Breast Cancer: Relationships With Survival

Abstract: Abstract Background Although physical activity has been consistently associated with reduced breast cancer mortality, evidence is largely based on data collected at one occasion. We examined how pre- and postdiagnosis physical activity was associated with survival outcomes in high-risk breast cancer patients. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
119
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(120 citation statements)
references
References 61 publications
0
119
0
1
Order By: Relevance
“…Leisure-time physical activity is associated with lower risks of 13 types of cancer [ 5 ], and exercise-associated reduction in breast cancer risk has been apparent in early-stage breast cancer patients [ 6 ]. In addition, high-risk breast cancer patients meeting the minimum Physical Activity Guidelines for Americans [ 9 ] experienced 50% reduced hazards of recurrence and mortality [ 7 ]. Therefore, epidemiological evidence supports that leisure-time physical activity and structured exercise before and after breast cancer diagnosis contribute to reducing the risk of breast cancer recurrence and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Leisure-time physical activity is associated with lower risks of 13 types of cancer [ 5 ], and exercise-associated reduction in breast cancer risk has been apparent in early-stage breast cancer patients [ 6 ]. In addition, high-risk breast cancer patients meeting the minimum Physical Activity Guidelines for Americans [ 9 ] experienced 50% reduced hazards of recurrence and mortality [ 7 ]. Therefore, epidemiological evidence supports that leisure-time physical activity and structured exercise before and after breast cancer diagnosis contribute to reducing the risk of breast cancer recurrence and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, those who performed comparatively lower levels of activity prediagnosis, during treatment, and postdiagnosis experienced similar benefits to those who performed higher levels of activity at each time point [159]. This indicates that even smaller amounts of regular physical activity yield significant benefits for this population [159]. It is also important to note that those who did not meet guidelines prediagnosis but met them 2 years postdiagnosis still experienced a 46% decreased risk of recurrence and 43% decreased risk of mortality [159].…”
Section: Exercise and The Gut Microbiotamentioning
confidence: 95%
“…Observational data demonstrates a linkage between self-reported exercise and reduced rates of development and recurrence of several cancers [156]. A prospective study of women with breast cancer found that meeting the minimum guidelines for physical activity both before and after diagnosis is associated with significantly reduced risk of recurrence or mortality [159]. Interestingly, those who performed comparatively lower levels of activity prediagnosis, during treatment, and postdiagnosis experienced similar benefits to those who performed higher levels of activity at each time point [159].…”
Section: Exercise and The Gut Microbiotamentioning
confidence: 99%
See 2 more Smart Citations